Sequence analysis of a non-classified, non-occluded DNA virus that causes salivary gland hypertrophy of Musca domestica, MdSGHV - Garcia-Maruniak, Alejandra (2008)
The genome of the virus that causes salivary gland hypertrophy in Musca domestica (MdSGHV) was sequenced. This non-classified, enveloped, double stranded, circular DNA virus had a 124,279 bp genome. The G+C content was 43.5% with 108 putative methionine-initiated open reading frames (ORFs). Thirty ORFs had homology to database proteins: eleven to proteins coded by both baculoviruses and nudiviruses (p74, pif-1, pif-2, pif-3, odv-e66, rr1, rr2, iap, dUTPase, MMP, and Ac81-like), seven to nudiviruses (mcp, dhfr, ts, tk and three unknown proteins), one to baculovirus (Ac150-like), one to herpesvirus (dna pol), and ten to cellular proteins. Mass spectrum analysis of the viral particles’ protein components identified 29 structural ORFs, with only p74 and odv-e66 previously characterized as baculovirus structural proteins. Although most of the homology observed was to nudiviruses, phylogenetic analysis showed that MdSGHV was not closely related to them or to the baculoviruses.